FIBRIN ACTIVATABLE UROKINASE (FA-UK): A LATENT FORM OF UK IN URINE RELATED TO A COMPLEX WITH AN INHIBITOR/FIBRIN-BINDING CO-FACTOR OF UK AND POSSIBLY OF PRO-UK - Dwivedi, C; Pannell, R; Gurewich, V (Thrombosis and Haemostasis, 1987)
The plasminogen activator activity in urine, expressed in IU, was found to be consistently 2-3 fold higher by fibrin plate assay than against amidolytic substrate (S-2444). Moreover, when the S-2444 assay was preceded by incubation of urine with soluble fibrin, a similar 2-3 fold increase in activity was found. The fibrin effect was dose-dependent and specific for various forms of soluble fibrin but not fibrinogen. The fibrin activatable activity was inhibited by antibodies to UK and was termed FA-UK. About 1/3 of the total UK activity in freshly voided urine was composed of FA-UK. The relative FA-UK content of urine was found to be enhanced by concentration. The FA-UK bound to fibrin/Celite. By gel filtration (S-200) of urine or by zymography, the MW of FA-UK was - 100K. Pretreatment of the samples with soluble fibrin prior to SDS-PAGE enhanced the amount but not the position of the FA-UK activity on the zymogram, indicating that the complex was not dissociated by fibrin. Pretreatment with hydroxylamine (1M) eradicated the FA-UK activity in urine. Addition of UK or pro-UK to urine followed by concentration (X10), increased the 100K band on the zymogram. Under conditions of this experiment, it was shown that little conversion of pro-UK to UK occurred suggesting that complexation occurs with pro-UK as well as with UK. Moreover, a - 100K FA-UK band on zymography was demonstrated afer addition of pro-UK to urine treated with DFP (5mM) or GGAck (20juM) to inactivate UK.It was concluded that a - 50K inhibitor in urine, with properties similar to an inhibitor described by Stump et al (JBC 261:12759, 86), acts as a co-factor for fibrin binding of UK and possibly also of pro-UK. It is speculated that this co-factor may contribute to the fibrin-specificity of pro-UK by localizing both it and its activated derivative, UK, to the fibrin surface.